PENGARUH MOTIVASI DAN PELATIHAN TERHADAP DINAMIKA KELOMPOKTANI DI KABUPATEN DONGGALA - Akrab, Ali (Fakultas Pertanian, Universitas Tadulako, 2024)
This study aimed to determine the effects of motivation and training, both simultaneously and individually, on the dynamics of farmer groups in Donggala Regency. The research utilized a survey method, including field observations, interviews, and questionnaires distributed to 66 farmers. Data were analyzed using multiple linear regression. The F-test demonstrated that motivation and training simultaneously had positively significant influence on the group dynamics. Specifically, the t-test results revealed: (1) motivation has a positive and significant effect on the farmer group dynamics, and (2) training also has a positive and significant effect on the group dynamics. The first hypothesis test (F-test) indicated that the combined effect of motivation (X1) and training (X2) on group dynamics in Donggala Regency yielded a regression value of 87.2, with an R² score of 76.0%. The second hypothesis test (t-test) showed that motivation (X1) significantly affects the group dynamics, with a t-value of 4.520 (α = 0.05). Training (X2) also significantly affects the group dynamics, with a t-value of 5.163, and a regression coefficient of 0.460, both at a significance level of 0.05.